The Participation of Village Consultative Body (BPD) in the Preparation of Regional Revenue and Expenditure Budget (APBD) in Rejosari Village, Negri Agung District, Waykanan Regency - Amay Lestari; Iskandar Ali Alam (Cita konsultindo, 2024)
This study aims to assess the participation of the Village Consultative Body (BPD) in the preparation of the Regional Revenue and Expenditure Budget (APBD) in Rejosari Village, Negri Agung District, Waykanan Regency. The study utilized a qualitative descriptive research method, using interviews and observations to collect data. The population of this study was all BPD members in Rejosari Village, with a sample of four members selected for the study. The study found that the management of village budgets in Rejosari Village was hindered by limited understanding among BPD members regarding budget preparation and suboptimal information management from the community. The study also found that the participation of BPD in the preparation of APBD was limited. Enhancing the participation of BPD and improving information management from the community are crucial to improving the management of village budgets in Rejosari Village. The study recommends increasing the capacity of BPD members and collaborating with external parties to manage information more effectively.